The jasmonate‐responsive AaMYC2 transcription factor positively regulates artemisinin biosynthesis in Artemisia annua. Issue 4 (10th February 2016) - Shen, Qian; Lu, Xu; Yan, Tingxiang; Fu, Xueqing; Lv, Zongyou; Zhang, Fangyuan; Pan, Qifang; Wang, Guofeng; Sun, Xiaofen; Tang, Kexuan
Summary: The plant Artemisia annua is well known due to the production of artemisinin, a sesquiterpene lactone that is widely used in malaria treatment. Phytohormones play important roles in plant secondary metabolism, such as jasmonic acid (JA), which can induce artemisinin biosynthesis in A. annua . Nevertheless, the JA‐inducing mechanism remains poorly understood. The expression of gene AaMYC2 was rapidly induced by JA and AaMYC2 binds the G‐box‐like motifs within the promoters of gene CYP71AV1 and DBR2, which are key structural genes in the artemisinin biosynthetic pathway. Overexpression of AaMYC2 in A. annua significantly activated the transcript levels of CYP71AV1 and DBR2, which resulted in an increased artemisinin content. By contrast, artemisinin content was reduced in the RNAi transgenic A. annua plants in which the expression of AaMYC2 was suppressed. Meanwhile, the RNAi transgenic A. annua plants showed lower sensitivity to methyl jasmonate treatment than the wild‐type plants. These results demonstrate that AaMYC2 is a positive regulator of artemisinin biosynthesis and is of great value in genetic engineering of A. annua for increased artemisinin production.